Determination Optimum Location of Outrigger and Belt Truss System in Tall Buildings with Non-Uniform Cross Section - Hamid Raeisi; Mohsen Malekinejad; Reza Rahgozar (مجله مدل سازی در مهندسی, 2018)
In this paper, optimum location of outrigger and belt truss system of tall structures with combined system of framed tube, shear core, outrigger and belt truss with non-uniform cross section of frame tube system along the height of structure is investigated. Framed tube and shear core under lateral loads are modeled as a cantilevered beam with box cross section using continuum approach. Effects of outrigger and belt truss systems shear core is modeled as a rotational spring placed at the location of belt truss and outrigger system. Relations for calculating deformations of the equivalent structure are obtained using moment area and superposition theories. Then, considering total energy of the system based on obtained relation of deformations and maximizing absorbed energy by equivalent spring, the optimum location of outrigger and belt truss in tall structures under triangularly distributed loads along structure’s height is obtained. In addition, the graphs are presented for different moment of inertia of frame tube system that can be used for determining optimum location of belt truss and outrigger system. Accuracy and efficiency of the proposed method is investigated by a numerical example and comparing the results with those obtained by computer analysis and other researchers. The results show that the proposed method reasonably accurate and optimum location is middle height of the structure.